Aktivitas Antidislipidemia Rebusan Daun Mangga Kultivar Manalagi (Mangifera indica L. Var. Manalagi) - Sulaeman, Agus; Susilawati, Elis; Aolina, Shelin (Pengurus Pusat Ikatan Apoteker Indonesia, 2022)
Abstract: Dyslipidemia is characterized by changes in lipid levels in plasma, a common indicator that is prone to the risk of cardiovascular disease. Plants that are suspected to have antidislipidemia activity, one of which is mango leaves. This study aimed to determine the effective dose in a decoction of mango manalagi leaves (Mangifera indica L. var. Manalagi) in decreasing levels of total cholesterol, triglycerides, LDL, and increasing HDL levels in high-fat feed-induced rats and propylthiouracil for 28 days. This research method was carried out preventively using 30 Wistar strain male rats which were grouped into 6 groups, namely negative control, positive control, comparison control (simvastatin 1.8mg/Kg BW), and a decoction test of manalagi mango leaves at a dose of 200, 400, 800 mg/kg BW. The parameters of the observed lipid profile are determined enzymatically using the micro lab. The results of the study on total cholesterol levels, showed the largest decreasing in the 200mg/kg BW dose group by 31.29%, in triglyceride levels the largest decreasing was found in the 400mg/kg BW dose group by 40.59%, in LDL levels the largest decreasing was found in the 200 mg/kg BW dose group by 48.03%, and in HDL levels there was the largest increasing in dose 800mg /kg BW of 97.40%. This study concludes that manalagi mango leaf decoction can be an antidyslipidemia in decreasing total cholesterol, triglyceride, and LDL levels as well as increasing HDL levels, with an effective dose of 200mg/ kg BW.